Relationships Between Work Stress and Job Satisfaction Among Nurses - Gelčytė, Vaida; Mažionienė, Asta (Slauga. Mokslas ir praktika, 2023)
The aim of this research – to analyze the stress experienced by nurses at work and their job satisfaction.The broad professional competencies of nurses, constantly changing and unpredictable situations, and increasing work demands often cause stress for nurses [2]. Based on the analyzed literature of foreign authors, it can be stated that the stress of nurses in the work environment is widespread, and the high level of stress is determined by workload, responsibility, conflictual relationships and excessive authority [3-4]. Research evidence has shown that working in a supportive environment is necessary to increase nurses' job satisfaction [1]. Therefore, it can be assumed that one of the factors determining job satisfaction is the stress experienced in the working environment.The study was conducted in 2022. from May to September, it was attended by 382 nurses working in health care institutions providing secondary and tertiary health care services. A quantitative research method was chosen. The questionnaire is based on standardized scales. The approval of the Ethics Commission of the Department of Nursing, Faculty of Health Sciences, Klaipėda University (No. 46Sv-S0-07) was obtained for conducting the study.Conclusions. The level of subjectively perceived stress of nurses was found to be higher than average. Nurses under the age of 50, with a university education and working for less than 10 years felt statistically significantly more stressed. Stress at work is caused by patient death and dying, heavy workload and problems with patients and their families. More than two thirds of nurses are moderately satisfied with their work. Job satisfaction was provided by the nature of work, management and relations with colleagues. The least satisfied were the salary, the possibility of recognition, the privileges granted and the work organization.
Keywords: nurse; stress; job satisfaction